Beyond Boundary: Challenging ecotourism in Indonesian wildlife reserves for the new future of orangutan conservation - Aprillyasari, Wulan Mayang; Rahman, Dede Aulia; Sunkar, Arzyana (Media Konservasi, 2024)
Orangutans exhibit significant potential as a key attraction for ecotourism centred around great apes. However, current tourist attractions primarily focus on national parks, neglecting the substantial opportunities present in wildlife reserves, particularly within Indonesia. This study seeks to investigate the feasibility of orangutan tourism activities in Lamandau Wildlife Reserve (LWR). Employing bibliometric analysis of primate tourism literature published in Indonesia from 2013 to 2023 using VOSviewer, complemented by an examination of national nature tourism policies, the research aims to elucidate the regulatory framework surrounding tourism in Indonesia wildlife reserves. The study engaged in interviews with individuals who frequently interact with orangutans in LWR through a combination of snowball technique and convenience sampling. Analysis of existing literature revealed a notable dearth of discussion pertaining to primate tourism studies in Indonesia, with a particular gap identified in the context of wildlife reserves. This oversight presents a missed opportunity, especially considering that prevailing national regulations allow the utilisation of wildlife reserve for ecotourism endeavours. To address this gap, it is imperative to align these domestic regulations with established international guidelines on primate tourism, aiming to mitigate potential tourism adverse impacts on primate populations. Assessing the tolerance levels of orangutans towards human presence in the LWR became a focal point, shedding light on the anthropogenic activities that are most compatible with orangutan behaviour. The research findings and methodologies employed hold promise in fostering the growth of orangutan tourism within Indonesia's wildlife reserves, simultaneously advancing orangutan conservation efforts and catalysing economic development within local communities.